2020
DOI: 10.47312/aefr.v5i01.457
|View full text |Cite
|
Sign up to set email alerts
|

The influence of brand image, Brand Personality and Brand Experience on Brand Love and Their Impact on Brand Loyalty of Cellular Card Users

Abstract: <p align="center"><strong>Abstract</strong></p><p>The purpose of this research is to know: (1) influence of brand image to brand love (2) influence of brand personality to brand love, (3) influence of brand experience to brand love (4) influence of brand image to brand loyalty (5) influence of brandexperience to brand loyalty, (6) the influence of brand love on brand loyalty. This research was conducted using a sample of 131 people and data are taken by giving respondents structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
2
3
1
Order By: Relevance
“…The results of this study are not in line with previous research, namely Dwiputranto (2017), where there is a significant positive effect between Brand Image and Brand Love. In addition, this research is also not in line with research by Achmad et al (2020), which states that Brand Image has a positive and significant effect on Brand Love. From the results of the discussion above, it can be concluded that Brand Image has a positive and insignificant effect on Brand Love, so hypothesis 1 is rejected.…”
Section: The Impact Of Brand Image On Brand Lovecontrasting
confidence: 95%
See 3 more Smart Citations
“…The results of this study are not in line with previous research, namely Dwiputranto (2017), where there is a significant positive effect between Brand Image and Brand Love. In addition, this research is also not in line with research by Achmad et al (2020), which states that Brand Image has a positive and significant effect on Brand Love. From the results of the discussion above, it can be concluded that Brand Image has a positive and insignificant effect on Brand Love, so hypothesis 1 is rejected.…”
Section: The Impact Of Brand Image On Brand Lovecontrasting
confidence: 95%
“…(Dwiputranto, 2017). This research is also in line with research conducted by Achmad et al (2020), which states that Brand Love has a positive and significant effect on Brand Loyalty. From the results of the discussion above, it can be concluded that Brand Love has a positive and significant effect on Brand Loyalty, so hypothesis 5 is accepted.…”
Section: The Impact Of Brand Love On Brand Loyaltysupporting
confidence: 91%
See 2 more Smart Citations
“…Place branding conceptualization is an intricate process that involves developing the marketing image of a city or region through various communication strategies (Achmad et al, 2020). This process aims to shape the perception and associations that target audiences have with the place, thereby increasing its competitiveness and attracting investment, tourism, and talent.…”
Section: Place Branding As a New Research Fieldmentioning
confidence: 99%